Flexible operation of post-combustion CO2 capture at pilot scale with demonstration of capture-efficiency control using online solvent measurements. (April 2018) - Tait, Paul; Buschle, Bill; Milkowski, Kris; Akram, Muhammad; Pourkashanian, Mohamed; Lucquiaud, Mathieu
Highlights: Datasets are produced for 7 dynamic operating scenarios at pilot-scale with coal-equivalent flue gas. Rapid introduction of steam to the reboiler on startup could reduce CO2 emissions by up to 13% over a 24 h period. Control of CO2 capture rate using in-situ lean solvent loading measurement and plant hydrodynamics is demonstrated. Abstract: Flexible post-combustion carbon capture and storage (CCS) has the potential to play a significant part in the affordable decarbonisation of electricity generation portfolios. PCC plant operators can modify capture plant process variables to adjust the CO2 capture level to a value which is optimal for current fuel cost, electricity selling price and CO2 emissions costs, increasing short-term profitability. Additionally, variation of the level of steam extraction from the generation plant can allow the capture facility to provide additional operating flexibility for coal-fired power stations which are comparatively slow to change output. A pilot-scale test campaign investigates the response of plant operating parameters to dynamic scenarios which are designed to be representative of pulverised coal plant operation. Online sensors continuously monitor changes in rich and lean solvent CO2 loading (30%wt monoethanolamine). Solvent loading is likely to be a critical control variable for the optimisation of flexible PCC operation, and since economic and operational boundaries can change on timescales 30 min or shorter, the development of methods for rapid, continuous online solvent analysis is key. Seven dynamic datasets are produced and insights about plant response times and hydrodynamics are provided. These include power output maximisation, frequency response, power output ramping and a comparison between two plant start-up strategies. In the final dynamic operating scenario, control of CO2 capture efficiency for a simple reboiler steam decoupling and reintroduction event is demonstrated using only knowledge of plant hydrodynamics and continuous measurement of solvent lean loading. Hot water flow to the reboiler is reduced to drop the capture efficiency. The "target" value for the minimum capture efficiency in the scenario was set at 30%, but a minimum CO2 capture efficiency of 26.4% was achieved. While there remains scope for improvement this represents a significant practical step towards the control of capture plant using online solvent concentration and CO2 measurements, and the next steps for its further development are discussed.